2000
DOI: 10.1183/09031936.00.16582400
|View full text |Cite
|
Sign up to set email alerts
|

Airway inflammation in patients with symptoms suggesting asthma but with normal lung function

Abstract: The hypothesis that eosinophilic airway inflammation is present in many patients presenting with respiratory symptoms suggestive of asthma but with normal lung function was tested. Thirty-six consecutive patients presenting with these features were studied. Twenty-five asthmatics and 43 healthy volunteers served as control groups. Signs of eosinophilic inflammation in blood and induced sputum were studied. Patients with respiratory symptoms were single-blindly treated with inhaled beclomethasone dipropionate (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

6
58
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 72 publications
(64 citation statements)
references
References 27 publications
6
58
0
Order By: Relevance
“…This demonstrates that treatment with an inhaled corticosteroid benefited the patients, even if they did not show a reversible airway obstruction at baseline or a marked PEF variability during the run-in period (mild hidden obstruction). The efficacy appears to be comparable to that shown in a 3-month study with beclomethasone dipropionate in a similar but smaller study population [13].…”
Section: Discussionsupporting
confidence: 61%
See 2 more Smart Citations
“…This demonstrates that treatment with an inhaled corticosteroid benefited the patients, even if they did not show a reversible airway obstruction at baseline or a marked PEF variability during the run-in period (mild hidden obstruction). The efficacy appears to be comparable to that shown in a 3-month study with beclomethasone dipropionate in a similar but smaller study population [13].…”
Section: Discussionsupporting
confidence: 61%
“…In a small pilot-type study, treatment with inhaled beclomethasone dipropionate for 3 months significantly reduced symptoms in patients in whom asthma was suspected, but lung function measurements did not confirm the diagnosis [13]. The present study evaluated whether these previous results could be repeated in a larger setting when patients were recruited on a multicentre basis.…”
mentioning
confidence: 94%
See 1 more Smart Citation
“…Our study showed that NAEB patients did experience acute exacerbations during the follow-up period. As mentioned previously, NAEB patients could have respiratory symptoms other than cough, such as chest tightness with wheezing, shortness of breath, and sputum production [8][9][10] . Treatment with systemic corticosteroids is occasionally required to relieve these symptoms 11 .…”
Section: Discussionmentioning
confidence: 99%
“…Previous longitudinal studies on NAEB have focused on the prognosis concerning relapse and the development of chronic airflow obstruction [5][6][7] . However, NAEB patients could have respiratory symptoms other than cough, such as chest tightness with wheezing, shortness of breath, and sputum production [8][9][10] , and treatment with systemic corticosteroids is occasionally required to relieve these symptoms 11 . No studies have yet investigated the incidence and predictors of acute exacerbations, defined as worsened respiratory symptoms requiring systemic treatment, in this condition.…”
mentioning
confidence: 99%